Liquidity and Solvency Analysis in Assessing the Financial Performance of PT Telkom Indonesia (Persero) Tbk Listed on the Indonesia Stock Exchange - Wahyuni; Musdalifah Hasmal; Siti Athirah Asmarani; Lilis Sukanda (Masterpiece, 2026)
This study aims to analyze the liquidity and solvency of PT Telkom Indonesia (Persero) Tbk, listed on the Indonesia Stock Exchange, in assessing its financial performance during the 2021–2025 period. The study employed a descriptive quantitative approach. The research object was PT Telkom Indonesia (Persero) Tbk, while the unit of analysis consisted of the company's audited consolidated financial statements for the 2021–2025 period. Secondary data were collected through documentation and literature review. The analysis employed liquidity ratios, namely the Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CaR), together with solvency ratios consisting of the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER). The findings indicate that the company's liquidity fluctuated throughout the observation period. The Current Ratio ranged from 0.777 to 0.886, the Quick Ratio from 0.763 to 0.875, and the Cash Ratio from 0.405 to 0.554. Despite these fluctuations, the company consistently maintained its ability to meet short-term obligations through effective management of current assets and cash resources. In terms of solvency, the Debt to Asset Ratio ranged from 45.46% to 47.69%, while the Debt to Equity Ratio ranged from 83.34% to 91.15%, indicating that the company's capital structure remained financially sound with a relatively controlled level of debt dependence. This study contributes to the literature by utilizing the most recent audited financial statements for the 2021–2025 period and integrating liquidity and solvency ratio analyses to provide a more comprehensive assessment of the financial performance of PT Telkom Indonesia (Persero) Tbk.